The American Revolution and the Law: Anglo-American Jurisprudence before John Marshall - Shannon C. Stimson (Princeton University Press, 2014)
This book is about the intellectual underpinnings of that most American of political phenomena - the transformation of political questions into legal ones. As such, it treats a subject at the intersection of jurisprudence, legal history and political theory. It is an attempt by someone trained as a political theorist and historian of ideas to offer a different conceptual vantage point from which to view the development of that peculiar and perhaps most problematic of American institutions, the Supreme Court exercising the power of judicial review. This study began life in some measure as an effort to solve a puzzle proposed by Gordon Wood, taking seriously his suggestion that the development of 'what came to be called judicial review' in America 'was not simply the product of their conception of a higher law embodied in a written document'. Certainly neither the writtenness nor fundamentality of law alone provided sufficient conditions for its development. Rather, it was 'different circumstances', and equally important, 'different ideas' which ultimately must have served to make the practice of judicial review both 'possible and justifiable' in America.1 In an effort to provide answers to the question of what circumstances and which ideas I chose to examine the locus of a particular mentalitd prevalent among revolutionary era colonials with regard to the proper source of knowledge and judgment about law. That locus was the jury. The trial jury in the Revolutionary era served a broader function than in either seventeenth or eighteenth-century England. Of course, from a methodological standpoint, to suggest the importance of such expansive jural powers among mid- and late eighteenth-century Americans is not to argue that either the particulars of jury practice or of commitments to them were uniform across all colonies. They were not, and each colony arrived at 1765 via its own particular experience with jural institutions. Yet, by the time the crisis engendered by the Stamp Act was in full force, the threat to jury trial stood out as a pre-eminent objection in the official and unofficial protests of revolutionary colonials in every colony but Virginia. By the 1770s, Virginia would 'catch up' and follow suit with its Declaration of Rights containing a guarantee of jury trial which would be most closely emulated by the later federal Bill of Rights.2 Equally important from an interpretive standpoint, colonial America's perceived attachment to jural institutions should be considered more than a case of revolutionary innovation.